Association between exclusive breastfeeding and postpartum post-traumatic stress disorder - Chen, Jingfen; Lai, Xiaolu; Zhou, Lepeng; Retnakaran, Ravi; Wen, Shi W.; Krewski, Daniel; Huang, Liping; Li, Meng; Xie, Ri-hua (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Research on the association between breastfeeding and postpartum post-traumatic stress disorder (PTSD) is sparse. This study aimed to examine the association between exclusive breastfeeding up to 42 days after childbirth and postpartum PTSD. Methods An epidemiologic study was conducted in a tertiary hospital in China between October 2019 and October 2020. Eligible mothers were recruited at 3 days after childbirth and assessed using the Post-Traumatic Stress Disorder Checklist – Civilian version (PCL-C) for PTSD at 42 days postpartum. The independent association between exclusive breastfeeding up to 42 days after childbirth and postpartum PTSD was estimated using log-binomial regression models, after adjusting for potential confounders. Results Ninety-two of 759 (12.1%) mothers developed postpartum PTSD within 42 days after childbirth. Compared with partially breastfeeding mothers, exclusively breastfeeding mothers had lower risks of postpartum PTSD (relative risk [RR] 0.28; 95% confidence interval [CI] 0.13, 0.59), re-experience (RR 0.48; 95% CI 0.30, 0.76), avoidance (RR 0.55; 95% CI 0.32, 0.97), and hyperarousal (RR 0.52; 95% CI 0.34, 0.78). After adjustment for family support, parity, mode of delivery, perceived birth trauma, early contact / suckling, and rooming-in, associations between exclusive breastfeeding and postpartum PTSD remained significant: the overall PTSD adjusted relative risk [aRR] was 0.31; (95% CI 0.15, 0.66), with a re-experience aRR of 0.48; (95% CI 0.30, 0.77) and hyperarousal aRR of 0.56; (95% CI 0.37, 0.85). Conclusion Exclusive breastfeeding up to 42 days after childbirth was associated with reduced risk of postpartum PTSD. While the potential for reverse causation cannot be ruled out, strategies to improve rates of exclusive breastfeeding through teaching, counselling, and support may benefit mothers and their infants by reducing the risk of postpartum PTSD.